Assessment of Ambient Exposures Firefighters Encounter While at the Fire Station: An Exploratory Study. Issue 10 (October 2017) - Sparer, Emily H.; Prendergast, Daniel P.; Apell, Jennifer N.; Bartzak, Madeleine R.; Wagner, Gregory R.; Adamkiewicz, Gary; Hart, Jaime E.; Sorensen, Glorian
Abstract : Objective: Firefighters are at an increased risk for many types of cancer. Although most studies on this topic focus on exposures encountered while fighting fires, exposures at the fire station are also cause for concern. This pilot study aimed to describe air quality within a few fire stations in and around Boston, Massachusetts, and to investigate physical and organizational factors that may influence levels of contaminants in stations. Methods: Air sampling of particulate matter less than 2.5 μm in diameter (PM2.5 ) and particle-bound polycyclic aromatic hydrocarbons (PAHs) was completed at four fire stations in Spring, 2016. Sampling occurred in the kitchen, truck bay, and just outside the station. Data were analyzed to assess differences between and within stations. Interviews ( n  =7) were conducted with officers at each station to explore health and safety-related organizational policies and practices. Interviews were transcribed and analyzed for thematic content. Results: At each station, levels of contaminants were higher in the truck bays than either the outdoors or kitchen, and varied the most throughout the day. The station with the highest exposures in the truck bay had the lowest levels in the kitchen, which was possibly explained by new building materials and effective separation between building zones. The age and layout of the stations appeared to determine the extent to which policies favoring exhaust capture were implemented. Conclusion: Levels of PM2.5 and PAH inside fire stations may contribute to firefighter cancer risk. Through understanding contaminant variability, we can begin to design and test interventions that improve cancer prevention.